The genus Limnoria (Limnoriidae, Isopoda, Crustacea) in Europe, including a key to species - Castelló, José (Zootaxa, 2011)
A new species of Limnoria inhabiting seaweed from the Alborán Island (western Mediterranean) is described. This is the seventh record of the genus from European coasts. L. turae n. sp. is mainly distinguished by the unique dorsal sculpture of its pleotelson, with 3 pairs of longitudinal carina without puncta, and the absence of the mandibular rasp. L. carinata is redescribed from a neotype. A key to European species is provided, and two comparative tables of the European species are included.